2013
DOI: 10.1016/j.devcel.2013.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Atg9 Interacts with dTRAF2/TRAF6 to Regulate Oxidative Stress-Induced JNK Activation and Autophagy Induction

Abstract: Autophagy is a highly conserved catabolic process that degrades and recycles intracellular components through the lysosomes. Atg9 is the only integral membrane protein among autophagy-related (Atg) proteins thought to carry the membrane source for forming autophagosomes. Here we show that Drosophila Atg9 interacts with Drosophila tumor necrosis factor receptor-associated factor 2 (dTRAF2) to regulate the c-Jun N-terminal kinase (JNK) signaling pathway. Significantly, depletion of Atg9 and dTRAF2 compromised JN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
87
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 68 publications
6
87
0
2
Order By: Relevance
“…These results are consistent with previous studies that show activation of the JNK pathway following ceramide stress as well as with ceramide/AP-1-dependent transcriptional activation of acid ceramidase following radiation therapy in prostate cancer cells (31)(32)(33)(34). JNK belongs to the larger group of mitogen-activated protein kinases and responds to a variety of signals including cytokines, radiation, heat shock, and autophagy (46,47). How CerS6 overexpression impacts on signaling pathways other than apoptosis largely remains to be determined.…”
Section: Discussionsupporting
confidence: 81%
“…These results are consistent with previous studies that show activation of the JNK pathway following ceramide stress as well as with ceramide/AP-1-dependent transcriptional activation of acid ceramidase following radiation therapy in prostate cancer cells (31)(32)(33)(34). JNK belongs to the larger group of mitogen-activated protein kinases and responds to a variety of signals including cytokines, radiation, heat shock, and autophagy (46,47). How CerS6 overexpression impacts on signaling pathways other than apoptosis largely remains to be determined.…”
Section: Discussionsupporting
confidence: 81%
“…The most obvious possibility is that CncC controls autophagy in response to reactive oxygen species. Previous studies have established that Drosophila utilizes a TRAF6/Atg9/Jun N-terminal kinase (JNK) stress pathway to activate autophagy upon oxidative stress provoked by hydrogen peroxide feeding (80,81). In concordance with those studies, we found no evidence that CncC activity is required for autophagy induced upon hydrogen peroxide feeding (results not shown).…”
Section: Discussionsupporting
confidence: 77%
“…Supporting this idea, we have found that Gyf is required for Atg1-Atg13-induced Atg9 puncta formation, which reflects active membrane trafficking to autophagosomes. 31,32 In addition, although Gyf does not control Atg1-induced Atg13 phosphorylation, it was necessary for Atg1-induced Atg13 puncta formation in developing eye discs, suggesting that Gyf may control autophagy by regulating subcellular localization of the Atg1-Atg13 protein complex.…”
Section: Discussionmentioning
confidence: 99%
“…4C and D), which are known to be accumulated during active autophagy. 31,32 We tested the requirement of Gyf in this process. Silencing of Gyf strongly abrogated the Atg9 puncta formation (Fig.…”
Section: Gyf Silencing Does Not Interfere With Ptdins3p Accumulationmentioning
confidence: 99%